Penguatan Peran Pengawas dan Penilik Sekolah melalui Pemahaman Mendalam tentang Urgensi Kegiatan Kepramukaan dalam Pengembangan Karakter Siswa: Strengthening the Role of School Supervisors and Inspectors through Deep Understanding of the Urgency of Scouting Activities in Developing Student Character - Amalliyah, Nor (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service activity aims to improve the understanding of school supervisors and inspectors throughout Lamongan Regency regarding the urgency of scouting activities in developing student character. The implementation of the activity employs an orientation approach through socialization and interactive training, which involves seminars, group discussions, and case studies. The material presented includes philosophy, methods, character values, and the role of supervisors and inspectors in supporting the implementation of scouting in schools. Evaluation was conducted using a pre-test and post-test, which demonstrated a significant increase in participants' understanding of all test instrument indicators, including basic scouting concepts, character values, active roles, implementation, and awareness of the positive impact of scouting on student character. This activity was facilitated by the Lamongan Branch Scout Movement and is expected to strengthen the role of school supervisors and inspectors in supporting character education through scouting in a sustainable manner.